2021
DOI: 10.1111/mcn.13160
|View full text |Cite
|
Sign up to set email alerts
|

Interventions supporting medical practitioners in the provision of lactation care: A systematic review and narrative analysis

Abstract: Most children globally are not breastfed to recommendations. Medical practitioners are frequently visited in the first 6 months post-partum, and the interaction at such visits significantly influences subsequent infant feeding decisions. Medical practitioners report that clinical practice in lactation is often disproportionately reliant on personal experience. This systematic review synthesises the literature on lactation health interventions used to support clinical decision making by medical practitioners. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…However, most significantly, there is little evidence to support the therapeutic efficacy of the range of fit and hold, or latch and positioning, interventions commonly applied by International Board Lactation Consultants or other health professionals, and these approaches remain predominantly experience or opinion based. 8 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most significantly, there is little evidence to support the therapeutic efficacy of the range of fit and hold, or latch and positioning, interventions commonly applied by International Board Lactation Consultants or other health professionals, and these approaches remain predominantly experience or opinion based. 8 11 …”
Section: Discussionmentioning
confidence: 99%
“…However, most significantly, there is little evidence to support the therapeutic efficacy of the range of fit and hold, or latch and positioning, interventions commonly applied by International Board Lactation Consultants or other health professionals, and these approaches remain predominantly experience or opinion based. [8][9][10][11] The physiologic approach to breastfeeding initiation, including skin-to-skin contact postpartum, has been a Box 1. The treatment of oral thrush in infants and painful breast and nipples in lactating mothers in an era of antifungal stewardship.…”
Section: If It's Not Thrush What Causes Burning Nipple Pain and Associated Radiating Breast Pain Including Between Feeds?mentioning
confidence: 99%
See 1 more Smart Citation
“…107 Much of what is offered women with breastfeeding difficulty, including interventions for fit and hold, is based upon experience or opinion ( Box 8 ). 2 , 108 111 In 2016, Thompson et al demonstrated in a retrospective analysis of the medical records of 635 mother–baby pairs that symmetrical apposition of the infant’s chin, cheeks and nose against the breast decreased nipple pain fourfold, compared with cross-cradle hold in which the mother used one hand to shape her breast as she brought the baby on. Although this study elucidated one aspect of fit and hold required to optimize intra-oral breast tissue volume, it does not offer explanatory biomechanical models or develop an evidence-base for a fit and hold intervention.…”
Section: Prevention and Management Of Lactation-related Nipple Painmentioning
confidence: 99%
“…Recent studies have indicated an increased focus on providing lactation education to health care providers 13,14 and have demonstrated that increased education can improve both the knowledge of breastfeeding management as well as impact attitudes toward breastfeeding support 15 . Many health care providers, however, continue to rely upon their own experiences rather than current evidence for clinical decision making when providing lactation support 16 …”
Section: Introductionmentioning
confidence: 99%